2022
DOI: 10.3390/d14070582
|View full text |Cite
|
Sign up to set email alerts
|

Community Governance, Financial Awareness, and Willingness to Participate in National Park Development: Evidence from the Giant Panda National Park

Abstract: Taking the Giant Panda National Park as an example, this paper uses factor analysis to measure residents’ financial awareness and mediating effect models to investigate the influence paths of community governance, financial awareness, and residents’ willingness to participate in the construction and development of national parks. Finally, it suggests potential solutions for national park development and biodiversity conservation. The results indicated that financial awareness and community governance levels ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, Indonesia's policy lacks cohesion regarding tourist policy on the national and national park governance inspire the people to promote biodiversity conservation. Furthermore, maintains the ecological balance and bequeathing natural heritage to generational generations (Feng et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…However, Indonesia's policy lacks cohesion regarding tourist policy on the national and national park governance inspire the people to promote biodiversity conservation. Furthermore, maintains the ecological balance and bequeathing natural heritage to generational generations (Feng et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Financially literate individuals can assess the legitimacy of digital financial service providers, detect fraud, and safeguard their financial information (Wu and Huang 2022). Studies show that higher financial literacy knowledge correlates with the easier use of digital platforms and conducting online transactions (Feng et al 2022). Although Buchdadi et al (2020) found a positive impact of financial literacy on financial access, their study did not specifically address digital financing.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Adoption of digital financial services enhances the operational effectiveness, facilitates finance access, improves risk management, and fosters innovation, boosting competitiveness (Butticè and Vismara 2022). Financial literacy also increases confidence in digital services (Feng et al 2022), motivating organisations to embrace them. Agro-SMEs can enhance financial decision-making and competitive performance by efficiently leveraging digital financial tools (Chen and Zhang 2021).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…and list several types of participation behaviors for respondents to choose. Another limitation is that external contextual factors were not fully considered in this study, such as the types of jobs provided by SJLNNR, individual health status (Feng et al, 2022), and distance to Shenjing Lake (Qiu et al, 2022). In addition, future research can be extended to specific types of protected areas, such as wetland protected areas.…”
Section: Limitations and Research Prospectsmentioning
confidence: 99%
“…On the one hand, some researchers have investigated the factors influencing the willingness to participate using the structural equation model (SEM). Feng et al (2022) used the Giant Panda National Park in China as an example, and their qualitative study reflected that community governance and financial awareness have a positive effect on the willingness of residents to participate. The three main factors of TPB (attitude, subjective norms, and perceptual behavioral control) can also influence the willingness to participate (Jia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%